SLIDING MODE CONTROL ON ISOLATED BRIDGES WITH COLUMNS OF IRREGULAR HEIGHTS USING POLE ASSIGNMENT AND PSO-SA HYBRID ALGORITHM - LEE, TZU-YING; CHEN, PO-CHUAN; JUANG, DER-SHIN (International journal of structural stability and dynamics, 2012)
The effectiveness of sliding mode control on the seismic response of an isolated bridge with columns of irregular heights, which exhibit hysteretic behaviors at both the columns and isolators, is studied. The bridge of concern consists of a two-span continuous deck and three columns of irregular heights, adjoining two single-span approaches each at the two ends. The irregular isolated bridge is idealized by an equivalent model to reduce the number of degrees of freedom involved. Compared with typical isolated bridges, the irregular isolated bridge has more poles of sliding surface, which dominates the dynamic characteristics of the controlled system and should be determined for the sliding mode control. The particle swarm optimization-simulated annealing (PSO-SA) hybrid searching algorithm is thus employed and shown to outperform the PSO algorithm and a parametric approach in finding the best sliding surface. Numerical simulations reveal that the sliding mode control together with the PSO-SA hybrid searching algorithm provides a simple and powerful technique for controlling the nonlinear seismic responses of irregular isolated bridges. Such a technique combining the control and optimization technology can be applied to practical bridges or structures, which are generally complicated and should be idealized by sophisticated numerical models.